The Relationship between Core Exercise and Balance in Footballers - Ozaslan, Ayhan (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
This research observed the impact of an 8 week-long core exercise program on the balance performance of footballers. A total of 40 players between the ages of 13-14 were included in the study, divided into two groups of 20 players, namely the Experimental Group (EG) and the Control Group (CG). While the EG performed 30 minutes of core exercise for two days a week over a total of eight weeks in addition to their usual exercises, the CG was only asked to maintain their usual routine. Before and after the study, a dynamic balance test was undertaken on the groups. To statistically analyze the data, the Variance Analysis Technique was applied to the Repeated Measurement Trials. According to the statistical analysis in terms of Anterior/Posterior, Overall Stability and Medial Lateral Balance, (pre- and post-test) x (right and left foot) (P = 0.039; P = 0.002; P = 0.034) and EG and CG x right and left foot (P = 0.000; P = 0.001; P = 0.002) interaction impacts were significant in terms of all three states of balance. In the determination of the right and left foot balance during the pre- and post-tests for the EG and CG, Tukey's multiple comparison test showed that the right foot balance of the EG was at a significantly higher level than their left foot balance in all three states of balance before the exercise. While the footballers had a better balance on their right feet in terms of anterior/posterior balance, there was no significant difference between the right and left feet of the footballers in terms of Overall Stability and Medial Lateral balances.